Collection of Plants in situ and Conditioning of Butia lallemantii Seedlings - Luciana Paim; Eduarda Avrella; Elisete Freitas; Claudimar Fior (Floresta e Ambiente, 2019)
ABSTRACT The objective of this study is to evaluate the survival and development of Butia lallemantii seedlings collected in situ. Seedlings were collected in Alegrete/RS, classified into four stipe diameter classes (SDC) and transplanted into polyethylene bags (2 L) filled with soil-based substrate, animal waste and rice husks. Evaluations were performed at four and eight months assessing survival, and leaf and root aspects after transplanting. The experiment was carried out in a completely randomized design with at least 50 plants per class. The results showed high survival rates for plants with larger stipe diameters, in addition to leaf emission, number of tillers, mature leaves, new roots and during decomposition. High number of new leaves was observed for SDC 2 and 3 (four months) and SDC 2, 3 and 4 (eight months). Therefore, greater survival and emission of vegetative structures were observed, especially in plants with higher diameter.